Tele-visionaries : - Webb, Richard C. (Wiley-Interscience, 2005)
This excellent publication provides a historical background of the dream of sight/sound extension by electric means and identification of the major participants is given. The book examines the foremost problem delaying the early progress of television and explores how the development of full-colour television by examining the inventions needed to achieve the dream, the people who produced them, the role of the motion picture industry, and more.